A geological interpretation of the Bouguer anomalies adjacent to the Churchill–Superior boundary in northern Manitoba - Gibb, R. A. (Canadian Journal of Earth Sciences, 1968)
The Bouguer anomaly map of nothern Manitoba and part of northeastern Saskatchewan was updated by a gravity survey in 1965. Density determinations of some 2000 Precambrian rock samples provide a sound basis for interpretation of the Bouguer anomalies in terms of relatively near-surface mass distributions in the upper crust. In some parts of the area there is excellent correlation between the surface rocks, their densities, and the Bouguer anomalies. The Nelson River gravity high outlines a belt of dense granulites. To the northwest three gravity lows are interpreted as the gravity effects of granitic intrusions, of which one is exposed at Split Lake and the others are largely subjacent, although their presence is supported by the occurrence of numerous mappable stocks of granite within the gravity lows. The Nelson River gravity high is separated from these lows by a steep gravity gradient, which marks a boundary between rocks of predominantly different ages (Hudsonian and Kenoran) between latitudes 54 °N and 56 °N. Age determinations are consistent with an interpretation of the Pikwitonei subprovince as an inlier of Kenoran age within the Churchill Province. The main Churchill–Superior boundary may then be moved south to what is at present the southern limit of the Cross Lake subprovince, which is a return to approximately the position originally selected by M. E. Wilson.